Cytoplasmic dynein is associated with slow axonal transport. - Dillman, J F (1996)
Neuronal function is dependent on the transport of materials from the cell body to the synapse via anterograde axonal transport. Anterograde axonal transport consists of several components that differ in both rate and protein composition. In fast transport, membranous organelles are moved along microtubules by the motor protein kinesin. The cytoskeleton and the cytomatrix proteins move in the two components of slow transport. While the mechanisms underlying slow transport are unknown, it has been hypothesized that the movement of microtubules in slow transport is generated by sliding. To determine whether dynein, a motor protein that causes microtubule sliding in flagella, may play a role in slow axonal transport, we identified the transport rate components with which cytoplasmic dynein is associated in rat optic nerve. Nearly 80% of the anterogradely moving dynein was associated with slow transport, whereas only approximately 15% of the dynein was associated with the membranous organelles of anterograde fast axonal transport. A segmental analysis of the transport of dynein through contiguous regions of the optic nerve and tract showed that dynein is associated with the microfilaments and other proteins of slow component b. Dynein from this transport component has the capacity to bind microtubules in vitro. These results are consistent with the hypothesis that cytoplasmic dynein generates the movement of microtubules in slow axonal transport. A model is presented to illustrate how dynein attached to the slow component b complex of proteins is appropriately positioned to generate force of the correct polarity to slide microtubules down the axon.